Analysis of acute non-pharmaceutical toxic exposures in children: a 5-year retrospective study - Qu, Yanning; Tang, Rui; Duan, Zhuyan; Sheng, Mengyi; Wang, Hui; Liu, Shuang; Li, Jiao; Guo, Linlin; Guo, Linying; Zheng, Si (Frontiers in Public Health, 2025)
ObjectiveThis study aims to systematically analyze the epidemiological characteristics, clinical interventions and outcomes of children with acute non-pharmaceutical toxic exposures.MethodsThis retrospective study included all children with acute non-pharmaceutical toxic exposure admitted to the emergency department of the Capital Institute of Pediatrics between January 1, 2019, and December 31, 2023. Eligible patients were triaged into red, yellow, and green groups according to their severity condition. Clinical information including demographics, exposure details, clinical manifestation, laboratory results, treatments, and outcomes were extracted from electronic medical records. Univariate and multivariate logistic regression analyses were conducted to identify risk factors associated with hospitalization.ResultsOverall, a total of 718 patients with acute non-pharmaceutical toxic exposures was included in this study, infants and toddlers accounting for 57.9%. The male-to-female ratio was 1.16:1. The majority exposure events occurred at home (89.3%) and in urban settings (78.4%). Accidental poisoning was the predominant cause, accounting for 94.7%, and the primary route of exposure was oral (93.6%). Mercury was the most common exposed substance, representing 18.8% of cases, particularly among preschool-aged children (31.7%). Patients triaged to red zone had a higher proportion of clinical manifestation and required more aggressive treatments. Although most patients discharged without treatment (78.4%), 19.1% need emergency observation, and 2.5% required hospitalization. Logistic regression analysis showed that corrosive household products exposure (OR = 42.747, 95% CI[5.041–362.520]), skin and mucosal damage (OR = 37.052, 95% CI[5.339–257.153]), pesticides exposure (OR = 33.322, 95% CI[3.863–287.423]), heavy metals exposure (OR = 31.636, 95% CI[1.471–680.210]), neurological manifestation (OR = 22.656, 95% CI[4.766–107.711]), positive toxicology results (OR = 15.105, 95% CI[6.584–34.656]), industrial products exposure (OR = 10.294, 95% CI[1.144–92.641]), and intentional poisoning (OR = 3.060, 95% CI[1.733–5.405]) associated with hospitalization.ConclusionPediatric patients exposed to some specific toxicants like industrial products and corrosive household products might associated with a higher risk of severe clinical outcomes. Advocating for enhanced safety regulations or educations and public health initiatives to mitigate the incidence of such exposures is still important for protecting children's health.